2017
DOI: 10.3390/ijerph15010038
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Naturally-Occurring Steroid Hormones in Raw Milk and the Associated Health Risks in Tangshan City, Hebei Province, China

Abstract: In recent years, high levels of hormone residue in food, capable of damaging the health of consumers, have been recorded frequently. In this study, 195 raw milk samples were obtained from Tangshan City, China, and the concentrations of 22 steroid hormones were measured by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). Cortisol was detected in 12.5% of raw milk samples (mean 0.61 µg/kg; range: Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
3
16
0
1
Order By: Relevance
“…In a study conducted on colostrum powder, E1 was found in the fat fraction, 7.59 µg/L, while in defatted milk and colostrum powder, E1 (5.51-15.0 µg/kg) and E2 (2.28-3.3 µg/kg) were detected with the total absence of E3 in different types of milk and colostrum powders [13]. In China, the absence of E1, E2, and E3 in all the analyzed milk samples was reported [15,18], while the estrogen concentration range of 0.05-3.2 µg/kg was found in milk samples that were analyzed in a different study [17]. For dairy products, estrone, 17β-estradiol, estriol, and 17αethynylestradiol were absent in all the analyzed samples [16].…”
Section: Comparison Of Meat-related Estrogen Exposure Among the Saudimentioning
confidence: 88%
See 2 more Smart Citations
“…In a study conducted on colostrum powder, E1 was found in the fat fraction, 7.59 µg/L, while in defatted milk and colostrum powder, E1 (5.51-15.0 µg/kg) and E2 (2.28-3.3 µg/kg) were detected with the total absence of E3 in different types of milk and colostrum powders [13]. In China, the absence of E1, E2, and E3 in all the analyzed milk samples was reported [15,18], while the estrogen concentration range of 0.05-3.2 µg/kg was found in milk samples that were analyzed in a different study [17]. For dairy products, estrone, 17β-estradiol, estriol, and 17αethynylestradiol were absent in all the analyzed samples [16].…”
Section: Comparison Of Meat-related Estrogen Exposure Among the Saudimentioning
confidence: 88%
“…Different analytical techniques have been applied for the determination of steroid hormones in biological samples/edible tissues. They include immunoassay [10], gas chromatography with mass spectrometric detector (GC-MS) [11,12], and liquid chromatography with mass spectrometric detector (LC-MS) [13][14][15][16][17][18][19]. Despite that immunoassay is widely used for measuring steroid hormones in biological matrices, an occasional lack of specificity is still a major drawback.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the above methods, the LC-MS/MS method has many outstanding advantages like simple sample preparation procedure, short analysis time, and, most importantly, the capacity of simultaneous analysis a large number of substances with high specificity, sensitivity and accuracy. Many publications have described the LC-MS/MS methods to simultaneously identify steroid hormones in milk and dairy product matrices [3][4][5]. Barreir et al determined six natural sex hormones (pregnenolone, progesterone, dehydroepiandrosterone, estrone, testosterone, and androstenedione) in infant formula [3].…”
Section: Introductionmentioning
confidence: 99%
“…The hormone estradiol, also known as 17β-estradiol, is a naturally occurring estrogen with high biological activity and is secreted mainly by female ovaries or male testes. Estradiol plays a vital role in many physiological processes [1]. Estradiol is an indicator of human sexual maturity.…”
Section: Introductionmentioning
confidence: 99%